OPTIMASI ADMINISTRASI KEPEGAWAIAN MELALUI SISTEM ABSENSI DAN PENGGAJIAN BERBASIS WEB (STUDI KASUS : PT. SELIM ELEKTRO BREBES - Anwarudin, Khairul; Dwi Hantoro, Gunadi; Saropah, Siti (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2025)
Selim Elektro is a company engaged in the manufacturing of household electronic appliances. The attendance and payroll systems at the company are still carried out manually. Each employee is required to sign daily attendance and overtime forms, which are previously distributed by the admin to the heads of each division. These forms are then collected daily by the division heads and submitted to the attendance administrator for manual entry into Microsoft Excel. With a large number of employees, this manual method has become inefficient in managing human resources. This condition often leads to errors in salary or wage distribution due to the vulnerability of the manual attendance system to recording mistakes and human error. Based on these issues, the author designed a web-based attendance and payroll information system using a localhost environment, which allows the attendance process to run automatically and have data integrated directly into the system. The web-based system was developed using a Lenovo ThinkPad laptop with an 8th-generation Intel Core i5 processor, supported by software tools such as Sublime Text and XAMPP, and utilizing the PHP programming language. The development of this system is expected to support the HR team's efficiency in managing employee attendance and payroll. Additionally, the system also provides convenience for employees to access information related to their attendance and salaries over a specific period.